Scenario Planning of Satellite Business Investment at Telkom Indonesia, Tbk - Risnando, Angga; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2017)
Abstract - The growth of technology, the ease of using applications, penetration of communication networks that cover all corners of the country and the dream to educate the nation with its existing technology capacity. Telkom as the largest telecommunication state-own company in Indonesia and one of the biggest in the Southeast Asia region should be able to provide the best service for the customer and nation particularly. Optical cables and submarine cables extending across most of Indonesia territory are still not able to serve these needs and also the risk of being disturbed is also high, moreover terrestrial radio that has only a maximum range of 30 kilometers and high operational costs. Therefore, Satellite is a very appropriate solution to overcome the above problems. The range is very wide, and can be able to unite the archipelago, but the satellite capacity owned by Telkom and other local satellite operators currently have not been able to serve all these needs. Scenario planning analysis is a method used to develop a strategy if a company has to face a situation such as changing in demand, changes in national and regional economic conditions, international expansion plans and investment plans over a period of time eg 5 years. Based on interviews with internal and external satellite business unit teams, there are several uncertain factors that can affect decision making such as "demand of transponder" and "business investment feasibility". Then those uncertainties is used as the axis to create 4 quadrants with high demand and low investment feasibility and then categorized into 4 types of scenarios, such as "ducking", "projection", "calming" and "growth" scenarios. From these four scenarios can be formulated three possible strategies that can be applied by the company when facing various conditions that will happen, the three strategies are major investment, option investment and operation focus.Keyword: Satellite, Transponder, Scenario Planning, Demand, Supply, Strategy